Location-Based Games as a Form of City Promotion: The Case Study of Pokémon GO and the Cracow Old Town - Gębica, Patryk (Journal of Public Governance, 2024)
Objective: Location-based games have been very popular for years, and the links they contain to places in the real world may raise questions about the quality of the content presented. The aim of the article is to present the possibilities of location-based games in the promotion of cities, using the example of the Pokémon GO game in the Old Town area of Cracow.Research Design & Methods: The research article is based on a literature review and content analysis of the Pokémon GO game in the Old Town of Cracow. As part of the study, players were asked to rate the portals in the mentioned game in the study area.Findings: There are over 250 portals of various characteristics in the Old Town of Cracow. Most of them, according to the respondents, are of high value and allow one to get to know the city better by playing Pokémon GO.Implications / Recommendations: This study may be important for city authorities who would like to better promote their areas that are often visited by players.Contribution / Value Added: The quality of POIs in the Old Town area of Cracow is quite high. The portals around the Wawel Royal Castle were particularly highly rated. Moreover, in the opinion of the respondents, portals presenting information boards and commemorative plaques are the most carefully prepared.Article classification: research articleJEL classification: L830